Co-designing behavioural public policy: lessons from the field about how to 'nudge plus'. (1st August 2021) - Richardson, Liz; John, Peter
Abstract : Background: Behavioural public policies, known as nudges, suffer from lack of citizen consent and involvement, which has led to an argument for more reflective nudges, known as 'nudge plus'.Aims and objectives: How can more citizen reflection be introduced in a way that is not itself top-down and paternalist in spite of good intentions? How might these 'nudge pluses' develop on the ground?Methods: This paper reports a mixed-methods case study.Findings: In the case study, there was an intervention that started off as a top-down nudge, using a randomised controlled trial. The nudge then evolved into a bottom-up initiative with citizen input aided by a design lab approach.Discussion and conclusion: One way to address tensions between top-down and bottom-up approaches is to let in the messiness and loss of direct control implied in a design lab, whereby nudge pluses might evolve naturally and without expert direction. The success of the eventual initiative points the way to more design-based nudge plus interventions. Nudge pluses may emerge naturally as a result of the evolutionary co-design process. There is potential for replication, with cross-fertilisation between different traditions by introducing behaviour change policies with a design-based approach.